Advancements in virtual reality for performance enhancement in combat sports: a mini-review and perspective - Li, Y.; Li, H.; Jiang, C.; Su, Y.; Jiang, S.; Zhang, G. (Frontiers in Psychology, 2025)
This mini-review examines the role of Virtual Reality (VR) in enhancing athletes` performance and reaction abilities in combat sports, aiming to highlight the advantages and potential benefits of VR technology for improving outcomes in various combat disciplines. We identified 13 relevant studies from the Web of Science and Scopus databases, encompassing disciplines such as fencing, taekwondo, karate, judo, and wrestling. The findings indicate that VR training can enhance athletes` sports skills and physical fitness, correct improper movements, provide training feedback, and, in some cases, surpass the effectiveness of traditional training methods. It also significantly enhances athletes` reaction capabilities. Even with these benefits, VR usage in combat training is still quite limited. Future research should focus on how to better leverage the advantages of VR technology in practical combat training for athletes, addressing the lack of tactile feedback, aiding athletes adapt to competition pressure caused by spectators, and examining whether there are gender differences in the use of this technology for training.